IMPLEMENTASI PENETAPAN PEMUKA DAN TAHANAN PENDAMPING (TAMPING) DI LEMBAGA PEMASYARAKATAN DITINJAU DENGAN PERMENKUMHAM NOMOR 9 TAHUN 2019 TENTANG PERUBAHAN ATAS PERMENKUMHAM NOMOR 7 TAHUN 2013 STUDI DI LAPAS KELAS IIB INDRAMAYU - Hardana, Nugraha Eka; Sumartini, Siti; Arifin, Jajang (Yustitia, 2023)
Penalties are sanctions given in the form of coaching, empowerment, and education to citizens who provide lessons and experience so that it may be a good thing in the future. Place of execution Punishment for perpetrators of criminal acts used to be referred to as imprisonment when they were converted into Detention Centers (RUTAN) and Penitentiaries (LAPAS). Prisoners and Prisoners in RUTAN and PRISONS are given fundamental life rights, personality formation and guidance. Coaching and guidance includes coaching and guidance activities, personality and independence. Carrying out the task of securing the number of officers is not ideal with the number of prison residents, let alone added with coaching and mentoring activities. Implementation of coaching activities and guidance of correctional officers assisted by Leaders and Detainees Companion (Tamping). Based on the above, it can be withdrawn. The problem is what is the position of the law-related leaders and tamping and the mechanism of determination and coaching are reviewed by PERMENKUMHAM RI No. 9 of 2019 concerning amendments to Permenkumham RI No.7 of 2013 in Class IIB Indramayu Prison? To answer questions, the author conducted research using juridical methods normative. This research focuses more on analysis than regulation existing legislation and other regulations using data- secondary data, namely scientific references or other scientific writings as material; Studies that can support the completeness of this scientific work. Implementation The determination of leaders and tamping in Indramayu Class IIB Prison is appropriate with PERMENKUMHAM RI No.9 of 2019 concerning amendments to Permenkumham RI No.7 of 2013. Surface and tamping Class IIB Indramayu Prison plays a role in terms of service, care for prisoners and people receiving mental health treatment coaching, considering the number of correctional officers, which is out of balance with the occupancy content of LAPAS. Rights inherent in leaders and tamping are the rights of prisoners.